Standardized Flow Cytometry Method for Absolute Counting of Intraepithelial Lymphocytes in the Intestinal Mucosa Using TruCountTM Beads - Corentin Joulain; Stéphanie Bessoles; Andrada Chiron; Guillaume Sarrabayrouse; Salima Hacein-Bey-Abina (Bio-Protocol)
In the intestinal epithelium, intraepithelial lymphocytes (IELs) coexist with intestinal epithelial cells (IECs). The IELs have an important role in defending the intestinal tract against pathogens and eliminating tumor cells. Anomalies in the absolute IEL count have been reported in various digestive diseases. IELs are typically counted using histologic techniques or under light microscopy after isolation of the epithelium. However, these techniques can introduce bias, which might account for the discrepancies in counts from one study to another. Here, we describe a flow cytometry assay for determining the absolute IEL count and the IEL/IEC ratio. We combined a conventional epithelial isolation method with a BD TruCountTM bead-based absolute counting technique to quantify IELs (CD45+ CD326/EpCAM- CD103+CD3+) and IECs (CD45- CD326/EpCAM+) in a C57BL/6 mouse model.